Desempenho agronômico e eficiência de utilização de nitrogênio por cultivares de milho - Souza, Cassiana Felipe de (Universidade Federal Rural do Semi-Árido, 2017)
Corn plays an important role in the social and cultural economy and development of several regions of Brazil. However, the productivity is considered low, being the management of nitrogen fertilization and selection of efficient cultivars in the use of nitrogen the main factors responsible for the low productivity of this crop. Thus, the objective of this work was to analyze the agronomic performance and efficiency of nitrogen use by corn cultivars for the production of green ears and grains. Two experiments were carried out, one to obtain green maize and another to corn grain, both in the didactic garden of the Department of Plant Sciences of the Universidade Federal Rural do Semi-árido (UFERSA), in the municipality of Mossoró-RN. The experimental design was in randomized blocks in a 2 x 3 factorial scheme, with five replications. The treatments consisted of the combination of two nitrogen doses (0 and 90 kg ha-1) and three corn cultivars (Cruzeta variety, Truck transgenic and AG 1051 hybrid). For green maize, we evaluated plant height and stem insertion, shoot diameter, dry mass of the plant, nitrogen, phosphorus and potassium accumulation, yield of green ears with straw and without straw and N efficiency indexes. For grain maize, we evaluated dry matter of the plant, nitrogen, phosphorus and potassium accumulation, grain yield and N efficiency indexes. In both experiments, the cultivars presented higher productive performance when fertilized with nitrogen and The AG 1051 hybrid was the most efficient in the use of nitrogen. The cultivars AG 1051 and Cruzeta presented the highest plant height and first spike insertion, and the cultivar Truck presented the highest leaf number and productivity. The highest accumulations of dry mass and NPK were observed in cultivars AG 1051 and Cruzeta. The leaves and the grains accumulated more nitrogen, whereas the stem and the cob accumulated more K. The cultivar Truck was the most indicated for the production of green corn
Agronomic performance and efficiency of nitrogen utilization by maize cultivars
Keywords: Zea mays; Produtividade; Nutrição mineral; Zea mays; Productivity; Mineral nutrition; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA